INTERPRETASI SEBARAN BATUBARA BERDASARKAN DATA WELL LOGGING DI DAERAH BLOK X PULAU LAUT TENGAH KABUPATEN KOTABARU - Julkipli, Julkipli; Siregar, Simon Sadok; Sota, Ibrahim (Lambung Mangkurat University Press, 2015)
Research has been done using well logging methods to interpreted coal distribution in the area BlockX Pulau Laut Tengah Kabupaten Kotabaru. Coal identification was changed ofkickongamma ray log chart which run to minimum value with seam A range from to 1,3 16,76 API, seam C range from to 5,02 12,44 APIand seam D range from to 0,56 7,38 API. Long density log which kick on chart run to maximum value with seam A range from to 1,16 1,39 gr/cm3, seam C range from to 1,60 1,74 gr/cm3and seam D range from to 1,82 2,22 gr/cm3. Resistivity log which kick on chart run to maximum value with seam A range from to 1.189,74 2.407,15 Ohm.m, seam C range from to 2.223,80 2.328,84 Ohm.m and seam D range from to 6,06 105,65 Ohm.m. Measurement ofcoal thickness is based on chart of long density and short density logs with seam A 0,16 119,55 m depth and 0,11 0,40 m thickness, seam C 0,20 52,89 m depth and 0,11 0,40 m thickness and seam D 0,21 37,13 m depth and 0,41 0,42 m thickness. Coal distribution has been strike N212°E and dip10°N302° E. Measurement method of coal resource was made two planes with volume measuredcoal resources about 2.273.792,69 tons.